COMPARATIVE FIGURATIVE LANGUAGES IN SONG LYRICS SEPANJANG HIDUP OF MAHER ZAIN - SITI JAMZAROH (Multilingual, 2019)
Abstract            This study aims to describe how figurative language is used in the lyrics of the song "Throughout Life" by Maher Zain. The methods used in this study include the provision of data, data processing, data analysis. Provision of data with record techniques and note taking techniques, data processing is done by classifying data based on the theory used. The results found are a) lexical metaphors consisting of comparisons of nouns, verbs, and nouns and adverbs; b) grammatical metaphors produce a comparison of common codes and unusual codes with meaning of passive-active, antimony, synonymy.